Synthesis of silver nanoparticles for antibacterial and larvicidal applications / Zainal Abidin Ali - Zainal Abidin, Ali (2017)
The present study deals with the green synthesis of silver nanoparticles (AgNPs) using the extract of plant. AgNPs were synthesized by reacting aqueous AgNO3 solution with apple extract (reducing agent). Synthesis conditions such as: ratio of silver salts/apple extract, reaction time, comparison of heating and non-heating method, surfactant as well as pH were investigated and optimized. The results of this investigation showed that AgNPs could be synthesized and optimized by controlling the synthesis conditions. The X-ray diffraction pattern confirmed the presence of only face centered cubic (FCC) Ag crystallites, and the dynamic light scattering estimates the average sizes of the AgNPs to be 5-150 nm. Fourier Transform Infrared (FTIR) as well as UV-vis spectroscopy identified ethylene groups as the reducing agent and capping agent for the formation of the AgNPs. The absorption maxima of the synthesized AgNPs showed characteristic Ag surface plasmon resonance (SPR) peak. The usage of surfactant has been observed to be an important parameter in controlling the shape and also play an important role in dispersing the AgNPs. Solution with pH 4 was found to be suitable in producing spherical shape of AgNPs. The AgNPs in suspension showed bactericidal activity of the AgNPs against Gram-negative and Gram-positive bacteria. Minimum bactericidal concentrations (MBCs) were found to be in the range of 15 g/mL to 1000 g/mL. Larvicidal activity of AgNPs against L4 Aedes aegypti was also determined. The AgNPs showed moderate larvicidal effects against fourth larval instar (LC50 = 15.76 ppm and LC90 = 27.70 ppm). In addition, comparison of larvicidal activity performance of AgNPs at high concentration prepared using two different methods showed that Ae. aegypti larvae was fully eliminated within 2.5 hours. This study has proven that green synthesis could provide an economic, eco-friendly, and clean synthesis route of the AgNPs.